2005
DOI: 10.1002/dmrr.572
|View full text |Cite
|
Sign up to set email alerts
|

A randomized multicentre trial of insulin glargine compared with NPH insulin in people with type 1 diabetes

Abstract: A single, bedtime, subcutaneous dose of insulin glargine provided a level of glycaemic control at least as effective as NPH insulin, without an increased risk of hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 12 publications
0
30
0
4
Order By: Relevance
“…Home and colleagues (2005) also found that once-daily insulin glargine produces a level of glycemic control comparable to that provided by once- or twice-daily NPH insulin, without an increased risk of hypoglycemia. However, treatment satisfaction and psychologic wellbeing were also evaluated in these patients (Witthaus et al 2001) and showed that insulin glargine has an advantage with respect to psychologic outcomes, as people are apparently more satisfied with treatment with insulin glargine compared with NPH insulin.…”
Section: Clinical Efficacy Of Insulin Glarginementioning
confidence: 81%
See 1 more Smart Citation
“…Home and colleagues (2005) also found that once-daily insulin glargine produces a level of glycemic control comparable to that provided by once- or twice-daily NPH insulin, without an increased risk of hypoglycemia. However, treatment satisfaction and psychologic wellbeing were also evaluated in these patients (Witthaus et al 2001) and showed that insulin glargine has an advantage with respect to psychologic outcomes, as people are apparently more satisfied with treatment with insulin glargine compared with NPH insulin.…”
Section: Clinical Efficacy Of Insulin Glarginementioning
confidence: 81%
“…Conventional longer-acting insulin preparations, such as NPH, have not provided consistent 24-hour cover, thus necessitating twice-daily administration in some individuals. NPH insulin also has an early peak at around 4 to 6 hours following subcutaneous injection and this can be associated with hypoglycemia, a limiting and potentially dangerous adverse effect (Home et al 2005). Insulin glargine is a recently developed, long-acting basal insulin that has been found to have a stable absorption rate without any pronounced peaks in plasma concentration, thereby providing near 24-hour cover (Heinemann et al 2000; Lepore et al 2000; Owens et al 2000; Scholtz et al 2005) (Fig.…”
Section: Clinical Efficacy Of Insulin Glarginementioning
confidence: 99%
“…Insulin glargine is a basal insulin with a duration of action of 20-24 h and a flatter effect curve than NPH insulin [5,6]. Several studies have evaluated the mean effect on HbA1c of insulin glargine compared with NPH insulin, but the results have been contradictory [7][8][9][10][11][12][13][14][15][16][17][18][19]. To the best of our knowledge, no studies have addressed any concept to study responders and non-responders for insulin glargine or any other types of insulins.…”
Section: Introductionmentioning
confidence: 91%
“…Intensive treatment aiming for normoglycemia delays the onset and slows the progression of retinopathy, nephropathy and neuropathy as well as reduces the risk for cardiovascular events [1,5,6]. Recent advances to improve glycemic control include switching to long-acting glargine insulin, which has proven to be safe and effective in patients with both Type 1 [7,8] and Type 2 diabetes [9,10]. Novel classes of oral antihyperglycemic drugs for patients with Type 2 diabetes, the insulin-sensitizing thiazolidinediones, selectively activate the nuclear transcription factor peroxisome-proliferator-activated receptor-γ (PPARγ ) [11].…”
Section: Glycemic Controlmentioning
confidence: 99%